Implementation of the Adventure Flashcard Game in German Vocabulary Learning in the Kulturreflektives Lernen Course at Universitas Negeri Malang - Angelina Indra Ayu; Rizman Usman (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2026)
This study aims to describe the implementation of the Adventure Flashcard game in German vocabulary learning for first-semester students of the German Language Education Study Program at Universitas Negeri Malang and to identify students’ responses. This study used a descriptive qualitative approach with 25 first-semester students of Offering A as research subjects. Data were collected through observation, semi-structured interviews, and documentation. The results show that the Adventure Flashcard game was implemented effectively through Guessing Game, Matching Game, and Flashcard Hunt activities. Students were actively involved and showed high enthusiasm during the learning process. The use of visual media helped students understand and remember German vocabulary more easily. In addition, students gave positive responses, indicating that the learning process was more engaging, enjoyable, and interactive. Thus, Adventure Flashcard can be used as an innovative learning media for German vocabulary learning.